Many-sided environment in Olympic sport - Сергей Бубка; Владимир Платонов; Мария Булатова; Наталия Коваленко; Тастанбек Есентаев (National University of Physical Education and Sport of Ukraine, 2017)
The analytical review article comprehensively examines various components of entourage in the Olympic sport - the environment surrounding athletes, which plays an important role in implementing and providing their preparation (training and competitive activities) and in a number of related areas which are of great importance for athletes both during their sports career and after its completion, as well as various aspects of the relationships between athletes and their environment (entourage)